Hemophilia B With Intracranial Hemorrhage Rehabilitation in High‐Dependency Unit: A Case Report - Xiaoyan Feng; Hongjun Zhu; Liying Han; Hongxing Xu; Lei He (Clinical Case Reports)
ABSTRACT Hemophilia B, an X‐linked recessive coagulation disorder, poses significant risks of life‐threatening intracranial hemorrhage (ICH). This case report details the multidisciplinary rehabilitation of a 41‐year‐old male with moderate hemophilia B (FIX activity: 3.9%) and ICH in a resource‐limited setting. Admitted to a high‐dependency unit postneurosurgical intervention, the patient received low‐dose prophylactic coagulation factor IX (maintained at 34.6%–66.2%) alongside real‐time coagulation monitoring. A stepwise rehabilitation protocol was implemented, including early passive joint mobilization, neuromuscular electrical stimulation, and progressive task‐oriented training, tailored to minimize bleeding risk. Over 7 weeks, the patient achieved marked functional improvement: Activity of Daily Living score increased from 0 to 80, modified Rankin Scale improved from 5 to 3, and Fugl‐Meyer Assessment (FMA) rose from 0 to 60, with no secondary bleeding. This case highlights the feasibility of integrating low‐dose prophylaxis with early rehabilitation in developing countries, offering a cost‐effective model to enhance functional recovery and reduce disability in hemophilia‐related ICH.